Analysis of The Role of Parents in Bringing Out Children's Talents Through The Application of The Gnoti Seauton Socrates Philosophy Method (Research Conducted on Parents of PIAUD Students in Cihanjawar Village, Purwakarta) - Enjang (International Conferences on Early Childhood Education Proceedings, 2024)
This research tries to apply the Socratic Gnoti Seauton Theory with a dialectical (dialogue) model as a parenting pattern at the early childhood age level, to determine its effect on increasing understanding of knowledge where this knowledge will lead children to discover awareness of their own 'self' (to" confession or knowing one self) in life. The method used is descriptive qualitative with a phenomenological approach through interview data collection, observation, documentation, literature study and data triangulation. The percentage of success in applying this theory shows that of the 35 children, 28 children (80%) experienced an increase, 5 children (14.29%) had no improvement, and 2 children ( 5.71%) were normal (no changes whatsoever). This shows that Gnoti Seauton theory or Socrates' dialogue (dialectic) model, if it is understood and applied well by parents, guardians (care givers) to their foster children or their children, will ultimately be able to make their foster children increase their understanding of the knowledge they have which will lead them to become humans who realize or recognize themselves (gnoti seauton).